Reduced circulating growth hormone and insulin-like growth factor-1 and delayed growth of premature rats are aggravated by longer daily duration of chronic intermittent hypoxia exposure - Zhang, Chi; Du, Xiaowan; Li, Jingjing; Zhang, Junbo; Yin, Guoping (Frontiers in Pediatrics, 2023)
Objective: This study mainly aimed to investigate the effect of daily duration of chronic intermittent hypoxia (CIH) exposure on circulating growth hormone (GH)/insulin-like growth factor-1 (IGF-1) concentrations and body weight changes of premature rats. Methods: 40 healthy male SD rats aged six weeks were enrolled in this study. These rats were randomly divided into four groups (n=10 per group), including normal control (NC) group (normal oxygen exposure every day), CIH-1 group (daily CIH exposure for 2 hours), CIH-2 group (daily CIH exposure for 4 hours), and CIH-3 group (daily CIH exposure for 8 hours). The serum GH/IGF-1 concentrations and body weights in all rats were determined after 30 days of normal oxygen or CIH exposure. Results: No significant difference was found with respect to the baseline body weight among the four groups of rats. After establishments of animal models with a duration of 30 days, significant differences were found respect to body weight, body weight changes, and serum GH/IGF-1 concentrations among the four groups of rats with a same trend (all P<0.05): the highest values were all in NC group rats, followed CIH-1 group, CIH-2 group, and CIH-3 group rats. Among all the rats, the body weight changes correlated significantly with both serum GH and IGF-1 concentrations (both P<0.05). Conclusion: CIH decreases circulating GH/IGF-1 concentrations and causes growth delay in premature rats. Such effects could be aggravated by increased daily duration of CIH exposures.